PENGGUNAAN MEDIA BENDA KONKRET DALAM MENINGKATKAN KEMAMPUAN MEMBILANG BANYAK BENDA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN SISWA KELAS 1 MI BAHRUL ULUM BULU KEDIRI - Istiana, Desy Putriarma (Journal Of Islamic Elementary School (JIES), 2018)
This study aims to determine the application of concrete media on the subject of mathematics in addition and subtraction material and to find out the ability to multiply many objects through the media of concrete objects in the mathematics subject matter of addition and subtraction of grade 1 students of MI Bahrul Ulum Kediri. The method of this research is Classroom Action Research (CAR) with the Kurt Lewin model which consists of two cycles with four stages, namely Planning, Implementation, Observation, and Reflection. Data collection techniques used were observation, interviews, documentation, and tests. The results of the study showed: The application of concrete objects in mathematics learning to counting the many material additions and subtraction of grade 1 students at MI Bahrul Ulum Kediri was running optimally. This can be seen in the final score of teacher activity increased from 62.5 with the unfavorable category in the first cycle to 96.09 with a very good category in the second cycle. Likewise, student activity increased from a score of 61.53 with an unfavorable category in the first cycle to 96.15 with a very good category in cycle II. Increasing the ability to count many objects through concrete media objects increases very well. This is evident in the pre-learning cycle of student mastery reaching 30% in the category of not good and the average reached 61.75. In the first cycle there was an increase of 60% with a fairly good category and an average of 71.25. There was an increase in the second cycle of student learning completeness reaching 90% with a very good category and the class average reached 86.25.